Penerapan Model Pembelajaran Project Based Learning Materi Penjumlahan Siswa Kelas 1 Sekolah Dasar Tlogosari Kulon 01 Semarang - Anggraeni, Pipin Novia; Miyono, Noor; Setyawati, Rina Dwi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study aims to describe the implementation of the project-based learning model in additional material. This research was conducted at SDN Tlogosari Kulon 01 Semarang. The type of research used is qualitative research with a narrative approach. The data of this research uses primary data and secondary data. Primary data were obtained from the homeroom teacher of class 1 and 5 students of class 1. Data collection techniques were observation, interviews, and documentation. Based on the results of observation and research, it is known that the teaching strategies carried out by teachers use learning models. This is evidenced by the results of interviews, observations, and documentation during the learning process in class. The implementation of the project-based learning model makes it easier for students to understand additional material. The activity steps contained in the project-based learning model provide learning experiences for students through project assignments. This is reinforced by the final results of student assessments in the evaluation questions given by the teacher. The success of the learning process requires a strategy through a learning model that has been implemented because it is effective in understanding the material and how to solve addition problems for grade 1 students.